Conserving shellfish reefs—a systematic review reveals the need to broaden research efforts. Issue 4 (14th May 2021) - Toone, Trevyn A.; Hunter, Rebecca; Benjamin, Emilee D.; Handley, Sean; Jeffs, Andrew; Hillman, Jenny R.
Abstract : Globally, shellfish reefs have experienced unprecedented declines from historical levels, imperiling the surrounding ecosystems and the services they provide. Shellfish conservation and restoration projects have emerged to combat and reverse this decline but are hindered by a scattered knowledge base and a lack of evidence‐based best practice. To address this concern, we conducted a systematic review of English‐language peer‐reviewed articles studying the impacts of conservation‐based actions on reef‐building bivalves. A comprehensive search identified 281 relevant articles for the review. Articles were then categorized to establish the temporal and geographic extent of shellfish reef conservation research, quantify collaboration within the field, and develop a systematic map of the distribution of evidence across intervention and outcome categories. The results confirm a substantial increase in shellfish reef research with 72% of articles published since 2010. However, this evidence base is uneven, with 80% of research occurring in the United States and Northern Europe, 71% on only oysters, and 58% by only academia‐affiliated authors. The systematic map of linkages and gaps also reveals disparities in the evidence base, as ecological interventions and outcomes are undertaken and measured at a far greater rate than social interventions and outcomes, despite evidence that social aspects are critical components of conservation work. To ensure future conservation practitioners have evidence that is relevant to the circumstances of their projects, this evidence base needs to be diversified and we offer recommendations on reprioritizations for future research as well as a comprehensive database of existing shellfish conservation papers.